Comparison of Outcome in Patients Undergoing Elective and Emergency Caesarean Section - Nadia Zahid , Iram Munawar, Amna Aslam , Sadaf Aleem Mirza (Journal of Rawalpindi Medical College, 2016)
Background: To study the frequency of complications after emergency and elective Caesarean Sections. Methods: In this prospective observational study all the female patients with age of 18-45 years, undergoing both elective and emergency Caesarean Sections (CS.) due to any reason were included. Patients were divided in two groups according to indications. Group A included emergency CS patients. Group B included elective CS patients. All the demographic details of the patients including gravidity, parity and indication for CS were noted. Patients in both groups underwent CS as standard procedure. Post-operatively, patients were assessed for wound infection, post-operative fever, spinal headache, respiratory Infection, thrombo-embolism Post-partum Haemorrhage (PPH) and other complications. Results: A total of 78 patients were included in the study. The mean age of the patients was found to be 29.8 ± 4.16 years. The mean gestational age was found to 34.79 ± 2.53 years in group A and 35.05 ± 2.41 years in group B. The frequency of complications was higher in emergency group than elective CS group. p-value was significant for post-operative fever, wound infection and PPH. Conclusion: The complication rate is higher in emergency CS than elective CS. It is required to look into factors for higher morbidity in emergency settings and need to take care of them.